The Influence of Workload and Work Environment on Job Satisfaction of UPT Abdulrachman Saleh Airport Malang Employees - Nur Lailatul Usryah; Yunus Purnama (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
One of the airports serving flights in Malang, East Java, precisely in Pakis, Kab. Malang is Abdulrachman Saleh Airport. Abdulrachman Saleh Airport is an airport managed by the East Java Provincial Government through the Technical Implementation Unit. The purpose of this study is to find out whether workload affects job satisfaction, does the work environment affect job satisfaction, does workload and work environment both affect job satisfaction, and how much workload and work environment affect job satisfaction Job Satisfaction of employees working at UPT Abdulrachman Saleh Airport Malang. This research is included in the group of quantitative research. The research was conducted at UPT Abdulrachman Saleh Airport Malang from 1 to 30 November 2022 where UPT Abdulrachman Saleh Airport Malang employees were the objects of this research. The source of the data used in this study was obtained from distributing questionnaires to the respondents of UPT Abdulrachman Saleh Airport Malang. The results of the study concluded that there was a significant influence between workload and work environment on job satisfaction of 26.8%.